Active Impedance Matching in Slender Continua via a Special PID Controller. Issue 1 (15th March 2018) - Krumm, Ludwig; Kreuzer, Edwin
Abstract: The concept of impedance matching is well known in electrical engineering and can be applied in mechanical engineering as well. Slender systems, which have a relatively low stiffness and should not be treated as a rigid body are typical candidates for the application of impedance matching. Impedance matching imposes a special boundary condition. In general, at the boundary of a slender mechanical system, waves are partially reflected. The goal of impedance matching is to minimize those wave reflections and to transmit the wave motion to the vicinity. In this paper, it is shown that the impedance matching approach has a great potential of damping vibrations and that a simple PID controller can be used to implement an active version. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)